Evaluation of mitochondrial and molecular derangements in cardiac adipose tissue during type 2 diabetes and relationship with cardiovascular risk - Nyawo, Thembeka Amanda (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.